Effectiveness of life skills training on self-efficacy and emotional intelligence among high school students in Urmia - Gheitarani, Bahram; Imani, Saeed; Sadeghi, Nina; Ghahari, Shahrbanoo (Social Determinants of Health, 2017)
Background: Life skills are the abilities to have adaptive and positive behaviors that enable human beings to deal effectively with the demands and challenges of life. The aim of the present study was to examine the effectiveness of teaching life skills on self-efficacy and emotional intelligence among high school students. Methods: A quasi-experimental study was conducted on 462 male high school students of Silvana area in Urmia city, selected via multi-stage cluster sampling method. These students studied in two different schools. Three classes were selected randomly from each high school and all the students of these classes completed the self-efficacy and emotional intelligence inventory. Participants who scored low on effectiveness of life skills training were selected for the study; among them 30 students were selected randomly and assigned randomly into two experimental and control groups (15 students each). The experimental group received life skills education but the control group did not receive any education. Both groups completed the Sherer's Self-Efficacy Scale and Bar-On Emotional Intelligence-Inventory in baseline and follow up phases. The data were analyzed using descriptive statistics (the mean and standard of deviation) and Multivariate analysis of covariance (MANCOVA). Statistical analysis was perfumed using IBM SPSS Statistics for Windows, Version 22.0. Results: The results of the study indicated that teaching life skills significantly increased mean±SD scores of self-efficacy (68.2±7.35, 55.4±9.96) and emotional intelligence (106.6±15.05, 94.8±11.33) in the experimental and control group, respectively (P=0.001). there were significant correlations between self-efficacy and academic achievement (r=0.518, P=0.01) Conclusion: Teaching life skills can improve students' self-efficacy and emotional intelligence and the education officials should pay attention to teaching these life skills to the students.